2021
DOI: 10.1007/s11901-021-00563-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Interventions in Liver Diseases: Focus on MAFLD and Cirrhosis

Abstract: Purpose of Review Dietary interventions (DI) aimed at improving overweight and metabolic abnormalities in metabolic dysfunction-associated fatty liver disease (MAFLD) and at reducing malnutrition and sarcopenia in cirrhosis should become part of routine care in hepatology. This review focuses on recent advances in this field. Recent Findings In patients with MAFLD, a gradual reduction, respectively, of 7–10% of body weight if overweight or of 3–5% if lean,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 125 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Various dietary patterns, nutrients, and food groups have been examined in the context of NAFLD and HCC, [15][16][17] although few studies have looked at HCC risk specifically in patients with NAFLD. Recently, a systematic review identified 30 observational studies (17 cohort, 7 case-control, 6 cohort with nested case-control subset) that focus on the association of food groups and dietary patterns with primary liver cancer, with 23 studies specifying HCC as the main outcome.…”
Section: Dietmentioning
confidence: 99%
“…Various dietary patterns, nutrients, and food groups have been examined in the context of NAFLD and HCC, [15][16][17] although few studies have looked at HCC risk specifically in patients with NAFLD. Recently, a systematic review identified 30 observational studies (17 cohort, 7 case-control, 6 cohort with nested case-control subset) that focus on the association of food groups and dietary patterns with primary liver cancer, with 23 studies specifying HCC as the main outcome.…”
Section: Dietmentioning
confidence: 99%